A Historical Survey of Fayun Monastery (法雲寺) in Bianjing (汴京) during the Northern Song Dynasty - Zong, Yanhong (Religions, 2024)
Fayun Monastery (法雲寺), a prominent Chan Buddhist monastery in Bianjing (汴京) during the Northern Song Dynasty, thrived for about half a century under the reigns of emperors Shenzong (神宗), Zhezong (哲宗), and Huizong (徽宗). Led by four generations of abbots—Yuantong Faxiu (圓通法秀), Datong Shanben (大通善本), Foguo Weibai (佛國惟白), and Fozhao Gao (佛照杲)—the monastery was esteemed by the royal family and influential in the development of the Yunmen School. This paper examines the monastery’s history through the tenures of its abbots, providing insights into the monastery’s significance in Northern Song Buddhism and its broader cultural and political context.